The multicultural challenge - Brochmann, Grete (Amsterdam ; London : JAI, 2003)
Cultural pluralisation - reinforced by immigration - has had major consequences for the political agenda in recent years in liberal democratic states. New types of tension have arisen - new forms of social and cultural differentiation, and new patterns of inequality. The diversity also reshapes the frame of reference for traditional policy instruments employed by modern welfare states: new issues arise that are linked to rights, legitimacy and policy measures of a general and targeted nature. This volume in the "Comparative Social Research" series addresses a number of issues related to this new diversity. Common themes are multiculturalism, power and integration, and these themes are analysed through a comparative lens.
Citizens of multicultural states : power and legitimacy / Grete Brochmann -- Integration nations ; the nation-state and research on immigrants in western Europe / Adrian Favell -- The shrinking inclusive capacity of the national welfare state : international migration and the deregulation of identity formation / Michael Bommes -- Comparing minority and majority rights: multicultural integration in a power perspective / Tordis Borchgrevink and Grete Brochmann -- The political representation of immigrants in Oslo and Copenhagen: a study of electoral systems and voting behavior / Joahnnes Bergh and Tor Bjørklund -- Political mobilization of ethnic minority women / Lise Togeby -- The trouble with difference: gender, ethnicity, and Norwegian social democracy / Anh Nga Longva -- The importance of being good: power and morality in Norwegian immigration politics / Anniken Hagelund -- What creed in Europe? Social exclusion, citizenship, and a changing EU policy agenda / Carl-Ulrik Schierup -- Ethnicity, social subordination and cultural resistance / Aleksandra ôlund -- From homogeneity to difference? Comparing multiculturalism as a description and a field for claim-making / Giuseppe Sciortino.
Includes bibliographical references.
Description based on print version record.
Keywords: Immigrants -- Cultural assimilation -- Europe -- Congresses; Immigrants -- Services for -- Europe -- Congresses; Immigrants -- Cultural assimilation -- Norway -- Congresses; Immigrants -- Services for -- Norway -- Congresses; Multiculturalism -- Europe -- Congresses; Multiculturalism -- Norway -- Congresses; Migration, immigration & emigration; Ethnic minorities & multicultural studies; Social Science -- Emigration & Immigration; Europe -- Emigration and immigration -- Government policy -- Congresses; Norway -- Emigration and immigration -- Government policy -- Congresses